2016
DOI: 10.1021/acs.jafc.6b00857
|View full text |Cite
|
Sign up to set email alerts
|

Promising Health Benefits of the Strawberry: A Focus on Clinical Studies

Abstract: The potential health benefits associated with dietary intake of fruits have attracted increasing interest. Among berries, the strawberry is a rich source of several nutritive and non-nutritive bioactive compounds, which are implicated in various health-promoting and disease preventive effects. A plethora of studies have examined the benefits of strawberry consumption, such as prevention of inflammation disorders and oxidative stress, reduction of obesity related disorders and heart disease risk, and protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
132
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(138 citation statements)
references
References 139 publications
1
132
3
2
Order By: Relevance
“…Beneficial effects of strawberry consumption comprise a wide range of biological activities, from antioxidant capacity to anti-inflammatory, anti-hypertensive, and anti-proliferative actions [11,12,19,41,42,43]. Epidemiological and clinical studies indicate that acute consumption of strawberry improves postprandial glycemic response, circulating inflammatory markers, and increases plasma antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beneficial effects of strawberry consumption comprise a wide range of biological activities, from antioxidant capacity to anti-inflammatory, anti-hypertensive, and anti-proliferative actions [11,12,19,41,42,43]. Epidemiological and clinical studies indicate that acute consumption of strawberry improves postprandial glycemic response, circulating inflammatory markers, and increases plasma antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some clinical studies observed that strawberry intake ameliorates some atherosclerotic risk factors by reducing circulating levels of vascular cell adhesion molecule 1 [13], and CRP [18,19], decreasing lipid peroxidation [19], and improving lipid profile [13,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Longerterm strawberry supplementation has been shown to improve multiple CVD risk factors (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), but less is known about the acute effects of strawberries in the context of a fat-containing meal. A modest attenuation of the 6-h postprandial triglyceride, insulin, and oxidized LDL response was found in overweight hyperlipidemic adults when 10 g freeze-dried strawberry powder was incorporated into a meal with 30 g total fat (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins, a category of phenolic flavonoids, are abundant in various fruits, vegetables and beverages and are commonly consumed in the human diet [2325]. Consumption of anthocyanins beneficially influences inflammatory disorders, the lipid profile, platelet activation and obesity-related disorders [2629]. Our previous studies have shown that purified anthocyanin supplementation reduces the levels of inflammatory biological markers and improves serum lipids and endothelial function [3032].…”
Section: Introductionmentioning
confidence: 99%